PENGARUH HARGA, PROMOSI DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN PADA SWISS-BEL HOTEL PANGKALPINANG - Dita Lestari; Hasanuddin Hasanuddin (JEM Jurnal Ekonomi dan Manajemen, 2021)
This study was conducted to analyze the effect of price, promotion, and consumer satisfaction on consumer loyalty. This research was conducted on guests who have stayed at Swiss-Belhotel Pangkalpinang Pangkalpinang by taking a sample of 193 people using an accidental sampling technique. The sample criteria are people who have stayed at Swiss-Belhotel Pangkalpinang because people with these criteria are considered to have been able to assess the hotel where they stay. The results of this study indicate that price has a significant effect on consumer loyalty, the promotion has a significant effect on consumer loyalty, and consumer satisfaction has a significant effect on consumer loyalty